2009
DOI: 10.1111/j.1440-1819.2009.01930.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of predictors of post‐ictal delirium after electroconvulsive therapy

Abstract: Aim: Although electroconvulsive therapy (ECT)often causes post-ictal delirium (PID), to date, the specific risk factors of PID have not been described. The purpose of the present study was therefore to elucidate the predictors of PID via identification of the characteristics of patients with PID.Methods: ECT was conducted in 50 patients and all patients underwent more than four sessions. A sine wave or a brief-pulse square wave ECT instrument was used. After convulsions the patients' PID was monitored for 30 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 10 publications
2
33
1
Order By: Relevance
“…This rate is similar to the rates reported in the literature [42] but another study reported that incidence of poct-ictal delirium (PID) was 24 % in patients without catatonic features and the incidence in patients with catatonic features was extremely high (88 %). This difference might be due to different definitions of PID and various factors such as age, diagnosis, stimulus properties [43]. The rate of prolonged seizure (11.5 %) found in our study is higher than the rates reported earlier in the literature [44].…”
Section: Discussioncontrasting
confidence: 78%
“…This rate is similar to the rates reported in the literature [42] but another study reported that incidence of poct-ictal delirium (PID) was 24 % in patients without catatonic features and the incidence in patients with catatonic features was extremely high (88 %). This difference might be due to different definitions of PID and various factors such as age, diagnosis, stimulus properties [43]. The rate of prolonged seizure (11.5 %) found in our study is higher than the rates reported earlier in the literature [44].…”
Section: Discussioncontrasting
confidence: 78%
“…It should be noted that we did consider serotonin syndrome due to concomitant use of venlafaxine and bupropion and ECT delirium as part of the differential diagnosis. PID is defined by Kikuchi et al 6 as an "acute confusional state, [which] can often occur during the immediate post-ictal phase in patients receiving ECT." Because ECT elicits seizures, patients may develop PID in about 10% of cases, although it has been reported in up to 36%.…”
Section: Discussionmentioning
confidence: 99%
“…Because ECT elicits seizures, patients may develop PID in about 10% of cases, although it has been reported in up to 36%. 6 Patients present with altered consciousness, disorientation, behavioral disturbances, and motor agitation. 7 The study published by Kikuchi et al 6 indicated that catatonic features may be an indicator for development of PID, because incidence of PID in these patients was as high as 88%.…”
Section: Discussionmentioning
confidence: 99%
“…Brief confusion following ECT or post-ictal delirium may occur following ECT. Catatonic features are predictors of post-ictal delirium and use of propofol may be useful as an alternative anaesthetic (Kikuchi et al, 2009) in this situation. The addition of manual hyperventilation during the early phase of ECT may also help to lessen the impact on immediate orientation following ECT, without impeding clinical response (Mayur et al, 2010).…”
Section: What Are the Side Effects?mentioning
confidence: 99%